ASPEK HUKUM PERJANJIAN ASURANSI PENUMPANG DALAM PENGANGKUTAN UDARA (Studi Pada PT Asuransi Jasa Raharja Cabang Medan) - SHERLY NOVITASARI SEMBIRING (University of North Sumatera, 2013)
Abstract : Therefore the more modern human life, it requires an insurer to support the sustainability of human life from the risk of unwanted. At this time, the average Indonesian people have never tasted a passenger from one of the Indonesian airlines. The thing that causes the government to continue to improve laws related to aviation insurance. So need to know about the following: the rights and obligations of the parties under the insurance agreement passenger air transport, replacement procedures and payment of insurance compensation passenger air transport, as well as dispute resolution in case of non-payment of compensation claims of air passengers. Kata Kunci: Asuransi Penumpang, Pengangkutan Udara